Plan para potenciación en gestión de residuos sólidos, cantones Balsas y Marcabelí, El Oro. - Martínez Pardo, Omar Alexander (My University, 2021)
The imminent increase in solid waste in the different regions of the world is the reason for the authorities to take emergency measures in the areas of solid waste management as a measure to curb this situation. Although the great powers of the world are the ones that generate the most, many of these countries are also great references in the efficient management of their waste. These countries achieve their objectives by involving political, legal, technical, and cultural factors. Therefore, it is necessary to position these projects as role models, apply them through the analysis of the local context and adapt their strategies to achieve efficient, sustainable, and environmentally friendly systems. In Ecuador, 172 of the Autonomous Decentralized Municipal Governments carry out direct waste management through their departments, 13 did so through municipal companies, 25 through the direct commonwealth, and joint public companies, and 10 provide the service in a combined manner. The practical work consists of carrying out a diagnosis of waste management, identifying the problems of this management, and developing the Plan for strengthening solid waste management in Balsas and Marcabelí counties for the optimization of the processes applied to improve quality. of life and the natural environment. This plan involves programs for the minimization, segregation, and storage of solid waste at the source, programs for the modernization of waste utilization processes, and steps for the acquisition of machinery.
El inminente incremento de los residuos sólidos en las diferentes regiones del mundo es motivo para que las autoridades tomen medidas de emergencia en los ámbitos de gestión de residuos sólidos como medida para frenar esta situación. Si bien las grandes potencias del mundo son los que más generan, muchos de estos países, también son grandes referentes en el eficiente manejo de sus residuos. Estos países logran sus objetivos involucrando a los factores de orden político, legal, técnico y cultural. Por lo tanto, es necesario posicionar a estos proyectos como modelos a seguir, aplicarlos mediante el análisis del contexto local y adaptar sus estrategias para alcanzar sistemas eficientes, sostenibles y ambientalmente amigables. En el Ecuador, 172 de los Gobiernos Autónomos Descentralizados Municipales, realizan una gestión directa de residuos mediante sus departamentos, 13 lo realizaban mediante empresas municipales, 25 mediante mancomunidad directa y empresas públicas mancomunadas y 10 prestan el servicio de forma combinada. El trabajo práctico consiste en realizar un diagnóstico de la gestión de residuos, identificar los problemas de esta gestión y desarrollar el Plan de potenciación de gestión de residuos sólidos en los cantones Balsas y Marcabelí para la optimización de los procesos aplicados para el mejoramiento de la calidad de vida y el entorno natural. Este plan involucra programas de minimización, segregación y almacenamiento de residuos sólidos en la fuente, tecnificación de procesos de tratamiento y aprovechamiento de residuos y gestiones para la adquisición de maquinaria.
Keywords: RESIDUO SOLIDO; SOSTENIBLE